Gambaran Derajat Trauma dengan Menggunakan AIS dan ISS pada Korban Kecelakaan di RS Labuang Baji - Sofyan, Riskawati Maulana; Anggraeni, Amelia Rezky; Sabiq, Mahmud; Mansyur, Mauluddin; Mathius, Denny; Assegaf, Zulfikar Gaffar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Traffic accidents are a leading cause of injury and death, particularly among individuals of productive age. This study aims to analyze injury patterns among traffic accident victims at Labuang Baji General Hospital, Makassar, during December 2024, utilizing data from Visum et Repertum (VeR). The Abbreviated Injury Scale (AIS) assigns severity scores to injuries across different body regions, while the Injury Severity Score (ISS) aggregates these scores to assess overall trauma severity. A retrospective research method was employed, analyzing medical records of accident victims. Collected data included injury locations and types, as well as AIS and ISS scores. Findings indicate that the majority of accident victims were motorcyclists of productive age, who are at higher risk for severe trauma. The most common injury was head trauma. AIS scores varied, with some patients sustaining injuries ranging from minor to severe. The average ISS indicated a level of trauma severity with a favorable prognosis. In conclusion, the application of AIS and ISS systems is effective in evaluating trauma severity among accident victims at Labuang Baji General Hospital. This information is crucial for planning medical management and allocating resources necessary for treating patients with varying degrees of injury severity and and compliance with the Road Traffic and Transportation Law.